Tremolo on Domra as a Means of Artistic Expression - BILOUSOVA, Svitlana (Studia Universitatis Babes-Bolyai Musica, 2023)
The article is devoted to tremolo as one of the most important techniques of playing the domra using a plectrum. The article analyzes the use of tremolo in the practice of performing on various instruments – struck string, string, wind instruments, piano. Tremolo on domra in modern performance is considered in several aspects – as a way to lengthen the sound and a specific coloristic technique. At the same time, a new look at tremolo as a special unique means of artistic expression is offered. The research angle focuses on auditory problems in the process of technical implementation of tremolo and the use of tremolo intensity as a means of overcoming inertial mechanical movements and negative perception of uniform sound. Using the example of modern works for domra and mandolin by Oleg Bezborodko, Valery Ivko, Yasuo Kuwahara, Evgen Milka, Oleksandr Oliinyk, Boryslav Stronko, the main functions of tremolos and the problems of their performance specification are considered.